Effect of anonaceous extracts on Aphis gossypii (Glover, 1887) (Hemiptera: Aphididae) and selectivity to Eriopis connexa (Germar, 1824) (Coleoptera: Coccinellidae) - Santos, Lindinalva dos; Trindade, Roseane Cristina Prédes; Santos, Djison Silvestre dos; Dias, Mirandy dos Santos; Broglio, Sônia Maria Forti; Lemos, Eurico Eduardo Pinto de (Acta Scientiarum. Agronomy, 2018)
The effects of ethanolic and hexanic extracts of soursop and sugar apple (EES, EHS, EESA and EHSA, respectively) on Aphis gossypii (Hemiptera: Aphididae) and its natural enemy Eriopis connexa (Coleoptera: Coccinellidae) by contact exposure, residual effect and ingestion tests were evaluated. The estimated LC50 and LC99 values for A. gossypii were 0.39% and 5.47% for (EESA); 0.23% and 1.19% for (EES); 0.47% and 4.39% for (EHSA); and 0.42% and 6.38% for (EHS), respectively. Considering contact exposure, EES at 0.23% was innocuous, and EHS at 0.42% was slightly harmful; for adult ladybugs, only EESA (5.47%) was classified as slightly harmful, with the other treatments classified as harmless. The results were similar for the residual effect. For selectivity in ingestion tests, EES and EHS at the LC50 did not affect the survival rate of the predator, but EESA (0.39% and 5.47% for the LC50 and LC99, respectively) reduced the survival rate to zero in less than 7 days, resembling chemical treatment with Decis®. Extracts applied to the eggs of an alternative prey reduced the consumption of eggs and therefore the predatory capacity of the ladybug, which led to a decrease in oviposition, egg viability and ultimately a reduction in predator fecundity. EES at a concentration of 0.23% was effective in the control of A. gossypii and was selective and did not affect the survival rate of the its natural enemy E. connexa.